The Need for a Sub‐L1 Space Weather Research Mission: Current Knowledge Gaps on Coronal Mass Ejections - Noé Lugaz; Nada Al‐Haddad; Bin Zhuang; Christian Möstl; Emma E. Davies; Charles J. Farrugia; Sahanaj Aktar Banu; Eva Weiler; Antoinette B. Galvin (Space Weather)
Abstract Over the past decades, missions at the L1 point have been providing solar wind and interplanetary magnetic field measurements that are necessary for forecasting space weather at Earth with high accuracy and a lead time of a few tens of minutes. Improving the lead time, while maintaining a relatively high level of accuracy, can be achieved with missions sunward of L1, so‐called sub‐L1 monitors. However, too much is unknown to plan for sub‐L1 monitors as operational missions: both the orbital requirements of such missions, and the achievable accuracy of forecasts based on their measurements have not been quantitatively defined. We review here some proposed mission concepts and explain the knowledge gaps related to coronal mass ejections (CMEs) that require a space weather research or science mission. We first show how STEREO‐A measurements in 2023 can be used as a proof of concept of the use of sub‐L1 monitor slightly off the Sun‐Earth line to forecast the Dst index. We then highlight that separations of ≲10° are needed to ensure that CMEs measured by a sub‐L1 monitor impact Earth. Next, we show that measurements with angular separations of ≲0.35° have negligible errors but separations of a few degrees can result in significant errors in lead time and in the forecasted magnetic field strength of CMEs. We also discuss how CME evolution over the last 0.05–0.2 au before impacting Earth is strongly under‐constrained and needs to be better understood before using measurements of sub‐L1 monitors for real‐time space weather forecasting.